BaCl2:Er3+—A High Efficient Upconversion Phosphor for Broadband Near‐Infrared Photoresponsive Devices. Issue 8 (9th May 2015) - Chen, Zhi; Jia, Hong; Zhang, Xiaowen; Liu, Jianmin; Zeng, Shengfeng; Li, Yang; Ma, Zhijun; Dong, Guoping; Qiu, Jianrong
Abstract : Utilization of photons with subband‐gap energy, mostly near‐infrared (NIR) photons, is highly desirable for photovoltaic cells; which can be achieved by adding an upconversion layer at the rear face of photovoltaic cells. Here, we study the upconversion luminescence properties of BaCl2 :Er 3+ phosphors and hexagonal NaYF4 :Er 3+ phosphors upon excitation of incoherent NIR sunlight with wavelength λ > 800 nm. Higher efficacious upconversion emissions of BaCl2 :Er 3+ phosphors have been observed in comparison with the well‐known hexagonal NaYF4 :Er 3+ phosphors. We demonstrate that the photocurrent response from the thin‐film‐hydrogenated amorphous silicon solar cell attached with the BaCl2 :Er 3+ phosphor is notably enhanced under irradiation of incoherent NIR sunlight with wavelength λ > 800 nm. This judicious design may be envisioned to shorten the distance for the remarkable improvement of the power conversion efficiency of the next‐generation photovoltaic cells and suggests a promising application for other NIR photoresponsive devices.